The International Symposium on Conservation and Utilization of Forest Resources (ISCUFR) - Ch'ng, Looi Chin (UiTM Sarawak, 2016)
The International Symposium on Conservation and Utilization of Forest Resources (ISCUFR) for Sustainable Livelihoods was carried out successfully at Mulu Mariott Resort and Spa, Mulu, Miri from 26th to 29th October, 201 5. The symposium, with the theme "Forests for food, medicine and ecological security", was supported by the Sarawak Convention Bureau and the Society for Conservation and Research Development of Medicinal Plants and International Consortium Of Contemporary Biologists, India. The event was officiated by The Honourable Datu Haji Len Talif Salleh, the Assistant Minister in the Chief Minister's Office (Promotion of Technical Education), and the Assistant Minister of Environment (Ministry of Resource Planning and Environment) representing The Honourable Datuk Amar Haji Awang Tengah Ali Hasan. Also present at the event were The Rector of UiTM Sarawak, Prof. Dato Dr. Jamil Hj Hamali and The Chair of the symposium, Prof. Dr. V Sivaram from Bangalore University, India.